Studi Faktor Lingkungan Fisik Rumah, Keberadaan Breeding Places, Perilaku Hidup Bersih, Pola Konsumsi Makan dan Kejadian DBD di Kota Semarang - Mawaddah Salwa; Nur Endah Wahyuningsih; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2016)
Dengue fever is a disease caused by dengue virus is classified Arthropod-Borne, genus Flavivirus and family Flaviviridae which enter into the circulation of human blood through the bite of Aedes aegypti or Aedes albopictus. The purpose of this research is to describe the physical environmental factors, breeding places, clean behavior, and food consumption patterns and the incidence of DHF in Semarang at the age of teens (12-25 years) in Semarang. This research is a descriptive observational cross-sectional study design. Sampling with purposive sampling method. The sample in this study is the DHF patients at the Regional General Hospital (RSUD) Tugurejo Semarang City General Hospital Center (RSUP) dr. Kariadi General Hospital (RSUD) of the City of Semarang, and telogorejo Hospital in March-May 2016 that met the inclusion criteria as well as those not DBD patients in Semarang in March-May 2016 with inclusion criteria of 80 people from total sampling. The results showed that the temperature in the house in a group of DHF mostly fit into the category of not at risk, while the humidity inside the house in groups instead of DHF patients are more at risk compared with patients with dengue. In the group of patients with DHF is still found larvae in breeding places and PHBS with good category higher than the category of bad. On the food consumption pattern adequate amounts of Fiber, Vitamin C, Calcium, and Proteins fit into the category of less.